Pemanfaatan Digital Marketing oleh UMKM Lombok Tengah dalam Masa Pandemi Covid-19 - Yunita Sari; Anjani Putri Jagat; Lalu Muhammad Rifki Nugraha; In Husnafiski Amrina Rosada (Program Studi Ilmu Komunikasi Universitas Mataram, 2021)
The decadency that happened due to the Covid-19 pandemic affected various sectors in life including the economic sector in Indonesia. Therefore, so many companies have to decrease their human resources which leads to layoffs. This makes so many people try to survive by starting small businesses or MSMEs. However, the social restriction enforced by the government creates even new problems. The pattern of consumers’ behavior, production, and the distribution of goods and services were forced to change due to the requirement of conducting most activities online. Hence, the MSME actors shift to the digital marketing technique to offset the requirement. The purpose of this study is to reveal whether digital marketing is beneficial for MSMEs in Central Lombok amid the pandemic. This research is using a qualitative descriptive method with a triangulation approach, a method that combines interviews and observation to check the data fact that will be processed. The subject of this research is MSMEs in Central Lombok that use digital marketing or online sales via social media and other online platforms. Using the 4Cs approach, the result shows that digital marketing happened to be highly beneficial for MSMEs in Central Lombok during the pandemic.